The Journalist Discourse on Political Corruption. a Comparative Analysis of the Sqm Case in Chile and the Bárcenas Case in Spain [el Tratamiento Periodístico Sobre la Corrupción Política. Análisis Comparado del Caso Sqm en Chile y del Caso de Bárcenas en España] - Sola-Morales, S (Universidad Compultense Madrid, 2017)
This empirical article analyzes qualitatively press coverage of political corruption in Spain and Chile. Specifically, the study focuses on the Chilean case "Soquimich" and in the Spanish case "Barcenas". For this purpose, the news discourse of Chilean daily El Mercurio and La Tercera and Spanish newspapers El País and El Mundo were compared regarding the following axes: 1) Role of the characters and characterization of them and 2) Discursive strategies underlayed by the media discourse. While there are differences in news coverage of corruption in both countries, the results obtained indicate that treatment of corruption is simplified and incomplete. That is because the stories analyzed are focused on corrupt-the particular characters-without questioning the real roots of corruption.
Keywords: Chile; Corruption; Discourse; Media; Spain